Infrared spectroscopic ellipsometry study of sulfur-doped In0.53Ga0.47As ultra-shallow junctions - Richard D'Costa, Vijay (2014)
Sulfur mono-layer doped In0.53Ga0.47As films were investigated by infrared spectroscopic ellipsometry. The complex dielectric function of doped layers shows free carrier response which can be described by a single Drude oscillator. Electrical resistivities, carrier relaxation times, and active carrier depths are obtained for the shallow n-In0.53Ga0.47As films. Our results indicate that sub-10 nm sulfur-doped layers with active carrier concentration as high as 1.7 × 1019 cm−3 were achieved. Sheet resistances estimated from infrared spectroscopic ellipsometry are in good agreement with those obtained by electrical methods.